Community involvement in the development and implementation of chronic condition programmes across the continuum of care in high- and upper-middle income countries: A systematic review. Issue 4 (April 2020) - Haldane, Victoria; Singh, Shweta R.; Srivastava, Aastha; Chuah, Fiona L.H.; Koh, Gerald C.H.; Chia, Kee Seng; Perel, Pablo; Legido-Quigley, Helena
Highlights: This review explores community involvement in mental health programmes which were described most often, and contrasts this with the sporadic evidence in other chronic conditions. Academic initiatives and government mandates are key drivers in community participation. Community participation can influence priority setting, can result in changes in behavioural changes in the community, and can bolster community resilience. Lessons learned include nurturing relationship strengthening and a phased approach where expectations, limitations and a transparent process are established; and trust is gradually built. Further research is needed to study contextual and health system factors influencing community participation, and to evaluate health outcomes. Abstract: Background: Community involvement is an important component of health programme development and implementation, including those focused on chronic condition treatment and management. Yet, few studies explore the manifestations of community involvement in chronic care programmes. Our review aims to examine the evidence on how communities are involved in planning and implementing chronic condition programmes in high and upper-middle income countries. Methods: Eligible studies included those that involved the community in the planning, implementation, monitoring and evaluation of health services, policy or health interventions. We searched Medline, Embase, Global Health, Scopus, and LILACs from 2000 to 2016, independently screened articles for inclusion, conducted data extraction, and assessed studies for risk of bias. Results: 27, 232 records were identified and after screening, 32 met inclusion criteria. We conducted a narrative synthesis to report on the forms and processes of community involvement used across mental health programmes and contrast this with the paucity of evidence on comparable programmes addressing other chronic conditions. Challenges reported included user factors, organisational factors, and social challenges such as stigma. Conclusion: Our review adds to the evidence supporting community involvement in chronic condition management and the processes that contribute to successful and sustainable involvement. We report on a model, derived from inductive analysis, that considers social and cultural components, organisational factors and stakeholder relationships as underpinning the development of community interventions across the care continuum.